The natural history of late diagnosed or untreated growing skull fractures: Report on two cases - Ziyal, IM; Aydin, Y; Turkmen, CS; Salas, E; Kaya, AR; Ozveren, F (Springer-Verlag Wien, 1998)
Growing skull fractures (GSF) are rare complications of head trauma. Cases after childhood are extremely rare and demonstrate complicated pathological conditions which necessitate extensive treatment. We report on two rare cases of intracranial cysts related to growing skull fractures which are secondary to trauma sustained during childhood, and have been discovered in adolescence.
Keywords: growing skull fracture; head trauma; skull fracture